2023
DOI: 10.3390/su15032057
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Framework for Developing a Smart-Tourism Destination in the Southeastern Adriatic–Ionian Area

Abstract: This paper presents a methodological framework aiming to support the creation of a smart-tourism destination. Specifically, the study is realised in the frame of NEST, a European Union Interreg project aiming to create a smart-tourism destination in the Adriatic–Ionian area. Therefore, the study focuses on the southeastern Adriatic–Ionian area, as a portion of the European macro-region including the Italian regions of Molise and Apulia and the Balkan countries of Albania and Montenegro. This area presents a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…A study carried out by Ndou et al (2023) found that a methodological framework that integrates different areas of analysis at technological, economic, tourism and resident levels facilitates tourist destination transformation into a STD. As stated by Buhalis et al (2023c), a STD enhances the tourism experience, increases the efficiency of tourism companies and cities and increases residents’ quality of life thanks to the interoperability between public and private organisations, researchers and local residents (Florido-Benítez, 2022b).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out by Ndou et al (2023) found that a methodological framework that integrates different areas of analysis at technological, economic, tourism and resident levels facilitates tourist destination transformation into a STD. As stated by Buhalis et al (2023c), a STD enhances the tourism experience, increases the efficiency of tourism companies and cities and increases residents’ quality of life thanks to the interoperability between public and private organisations, researchers and local residents (Florido-Benítez, 2022b).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Fourth and last, since the six Spanish smart destinations were certified as STDs, we implemented updated data (2015–2022) from INE (2020, 2023a, 2023b), AENA (2023), EU (2020, 2022), SEGITUR (2020, 2023), Spanish Secretary of State for Tourism (2023) and Smart Tourist Destinations (2023a, 2023b) organisations to analyse the most important tourism demand and supply indicators (see Figures 3 and 4) and how these have impacted the territory. We selected in this research the number of passenger arrivals (Florido-Benítez, 2023a, 2023b), hotel and room indicators (Ndou et al, 2023; Perić et al, 2022) and hotel occupancy rate indicators (Benítez-Aurioles, 2022a) because these are the most frequently used measures of tourism demand and supply. Aguirre et al (2023) note that the number of hotel and room, hotel occupancy rate and passenger and tourist arrival indicators are necessary to measure the sustainability in STDs (Gehlot & Singh, 2022; Zamorano et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The research method used in this study is a quantitative approach using the Smart Partial Least Square (PLS) method as a data analysis tool [10], [11]. The quantitative approach was chosen to measure the extent of the influence of smart automation in smart tourism industry management on tourist destination loyalty and sustainable development using numerical data generated from questionnaires [12], [13], as shown in Table 1 However, I had a somewhat unpleasant experience in this city. BOTJ4…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the concept of STDs or SDs has emerged as a principle of innovation and competitiveness in global tourism markets, with the vision of developed countries based on another concept, SCs [9,29].…”
Section: Conceptual Approachmentioning
confidence: 99%